1996
DOI: 10.1111/j.1365-2133.1996.tb16218.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and prognosis of subungual melanoma in 34 Japanese patients

Abstract: The incidence of malignant melanoma is much lower in the Japanese than in caucasians. However, amongst the various types of malignant melanoma, the subungual and periungual sites are commonly found in the Japanese. One hundred and fifty-one cases of cutaneous malignant melanoma were seen over a 25-year period at our hospital. We found that, in 34 patients (23%), the subungual region was involved, a high frequency for one institution. We have analysed these patients and looked at their treatment. The finger nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
27
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 16 publications
6
27
3
Order By: Relevance
“…1,4,13,18,19 Comparing the characteristics of our group of patients with other studies, age and gender distributions agreed largely with those reported previously in NAM. 2,13,19,20 In agreement with other literature, the most frequent primary clinical signs that were observed by our patients were nail and/or periungual pigmentations (longitudinal melanonychia, Hutchinson sign). 18 Nail and periungual pigmentation is not specific for NAM but can be observed regularly in early and advanced stages, sometimes many years before establishment of a mass that led to making the diagnosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1,4,13,18,19 Comparing the characteristics of our group of patients with other studies, age and gender distributions agreed largely with those reported previously in NAM. 2,13,19,20 In agreement with other literature, the most frequent primary clinical signs that were observed by our patients were nail and/or periungual pigmentations (longitudinal melanonychia, Hutchinson sign). 18 Nail and periungual pigmentation is not specific for NAM but can be observed regularly in early and advanced stages, sometimes many years before establishment of a mass that led to making the diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…[21][22][23] As expected, we found acrolentiginous melanoma to be the most frequent histological type. 3,13,19,20 In our study, mean ± SD TT of the melanomas (3AE95 ± 2AE58 mm) and a high rate of ulcerated tumours were within the range of the data reported elsewhere, 13,19,20 indicating late recognition, diagnosis and treatment in comparison with other melanomas of the skin. It can be assumed that late diagnosis per se might be responsible for the unfavourable prognosis rather than the specific tumour location.…”
Section: Discussionsupporting
confidence: 78%
“…125 In a small series, systemic treatment with dacarbazine, vincristine, and nitrosourea was credited with improving prognosis. 102 Overall, the prognosis in cases of melanoma of the nail unit is poor, although there are trends to show that this is improving, namely from earlier diagnosis and more in situ and superficial tumors. Surgical extirpation remains a challenge.…”
Section: Melanoma and Melanoma In Situmentioning
confidence: 97%
“…A study of nail unit melanomas in Japanese patients compared survival rates in the periods 1969-1982 and 1983-1993. 102 The 5-year survival rates increased from 53% to 87%, respectively. The authors credited this dramatic progress to greater public awareness (and discovery of thinner melanomas) and to the introduction of improved chemotherapy.…”
Section: Melanoma and Melanoma In Situmentioning
confidence: 98%
“…2,4 Prognosis in nail melanoma is related to tumor depth 1-3 and biological grade 2 but not to histological type. 3 One of the greatest difficulties is delayed diagnosis related to correct clinical and, sometimes, histological identification.…”
mentioning
confidence: 99%